Ionic speciation and risks associated with agricultural use of industrial biosolid applied in Inceptisol - Barros Trannin, Isabel Cristina de [UNESP]; Artur, Adriana Guirado; Siqueira, Jose Oswaldo; Souza Moreira, Fatima Maria de (Springer, 2019)
The evaluation of the chemical leaching potential from soils amended with biosolid is of extreme importance for environmental safety of agricultural use of these residues. The objective of this study was to evaluate the polluting potential and possible risks associated with the agricultural use of biosolids generated by the polyethylene terephthalate (PET) fiber and resin industry through ionic speciation and analysis of the activity of chemical species present in the leached solution from Inceptisol treated with rates 0, 6, 12, 18, 24, 48, 96, and 144Mgha(-1) on dry basis. The experiment was conducted in a lysimeter and the treatments with three replications were distributed at random. Chemical leaching was made by application of CaC1(2) 0.01molL(-1) solutions in a volume fourfold higher than the water retention capacity of the soil, divided into five leaching events: 210, 245, 280, 315, and 350days of incubation. Chemical species concentrations in collected leachates were used for ionic speciation by geochemical software Visual MINTEQA2 version 4.0. Impact factor of chemical species was calculated as the ratio between maximum concentration in the leach solution in the treated soil and control. Dissolved organic carbon had strong influence on Pb+2 and Cu+2 leaching, but these elements in free or complexed forms presented low activities in solution. Leaching of NO3-, Zn+2, and Na+ represents the main environmental risk of agricultural use of this residue. However, these risks can be minimized if technical criteria and critical limits for the agronomic use of biosolids were observed.
Keywords: Chemical species; Leaching; Organic residues; Pollution